Prevalence and Risk Factors Associated with Precancerous Cervical Cancer Lesions among HIV-Infected Women in Resource-Limited Settings. (4th April 2012) - Memiah, Peter; Mbuthia, Wangeci; Kiiru, Grace; Agbor, Solomon; Odhiambo, Francesca; Ojoo, Sylvia; Biadgilign, Sibhatu
Abstract : Objective . To assess the prevalence and identified associated risk factors for precancerous cervical cancer lesions among HIV-infected women in resource-limited settings in Kenya. Methods . HIV-infected women attending the ART clinic at the Nazareth Hospital ART clinic between June 2009 and September 2010. Multivariate logistic regression model with odds ratios and 95% confidence intervals (CI) were estimated after controlling for important covariates. Result . A total of 715 women were screened for cervical cancer. The median age of the participants was 40 years (range 18–69 years). The prevalence of precancerous lesions (CINI, CINII, CIN III, ICC) was 191 (26.7%). After controlling for other variables in logistic regression analysis, cervical precancerous lesions were associated with not being on ART therapy; whereby non-ART were 2.21 times more likely to have precancerous lesions than ART patients [( aOR ) = 2.21, 95% CI (1.28–3.83)]. Conclusion . The prevalence of precancerous cervical lesions was lower than other similar settings. It is recommended that cancer screening of HIV-infected women should be an established practice. Availability and accessibility of these services can be done through their integration into HIV. Prompt initiation of HAART through an early enrollment into care has an impact on reducing the prevalence and progression of cervical precancerous lesions.